Structure based design of macrocyclic factor XIa inhibitors: Discovery of cyclic P1 linker moieties with improved oral bioavailability. Issue 19 (1st October 2019) - Clark, Charles G.; Rossi, Karen A.; Corte, James R.; Fang, Tianan; Smallheer, Joanne M.; De Lucca, Indawati; Nirschl, David S.; Orwat, Michael J.; Pinto, Donald J.P.; Hu, Zilun; Wang, Yufeng; Yang, Wu; et al.
Graphical abstract: Abstract: This manuscript describes the discovery of a series of macrocyclic inhibitors of FXIa with oral bioavailability. Assisted by structure based drug design and ligand bound X-ray crystal structures, the group linking the P1 moiety to the macrocyclic core was modified with the goal of reducing H-bond donors to improve pharmacokinetic performance versus 9 . This effort resulted in the discovery of several cyclic P1 linkers, exemplified by 10, that are constrained mimics of the bioactive conformation displayed by the acrylamide linker of 9 . These cyclic P1 linkers demonstrated enhanced bioavailability and improved potency.